2009
DOI: 10.1111/j.1469-7610.2009.02124.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between language development and behaviour problems in children with hearing loss

Abstract: Behaviour problems are found more commonly in children with hearing loss and the level of behaviour problems is highest amongst those children with hearing loss with the least developed language capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
103
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 19 publications
(21 reference statements)
13
103
0
Order By: Relevance
“…Its early identification is crucial not only to ensure an adequate language development of children but also to allow the development of their cognitive, relational, social, and even scholastic skills [1,98,99,107] . The diagnostic work-up is often complicated either in order to define the hearing threshold level, either to the identification of the hearing loss etiology, when possible [1,110] ; the latter could indicate, more appropriately and when possible, the best therapeutical-rehabilitative process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its early identification is crucial not only to ensure an adequate language development of children but also to allow the development of their cognitive, relational, social, and even scholastic skills [1,98,99,107] . The diagnostic work-up is often complicated either in order to define the hearing threshold level, either to the identification of the hearing loss etiology, when possible [1,110] ; the latter could indicate, more appropriately and when possible, the best therapeutical-rehabilitative process.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of hearing aids is related to their fitting and particularly to the quantity of speech and spectral information transmitted to the central auditory system [99] . Since (i) the earliest diagnosis of hearing disorders, and (ii) the availability innovative technologies (particularly in terms of advanced hearing aids solutions), a progressive improvement of the rehabilitative results achieved in children affected by moderate-severe hearing loss has been observed in the last years [37] .…”
Section: Hearing and Speech Therapy Rehabilitationmentioning
confidence: 99%
“…Our study adds two important findings: Firstly, psychosocial difficulties seem to appear as early as in preschool age, which has important implications for early intervention planning. Secondly, the finding that psychosocial problems are apparent even after controlling for receptive vocabulary suggests that although language plays an important role in psychosocial functioning (Stevenson, McCann, Watkin, Worsfold, & Kennedy, 2010), additional mechanisms significantly affect development in HH children. This finding is supported by who found communication abilities, but not vocabulary or syntax skills, to be related to psychosocial functioning in preschool children with hearing loss.…”
Section: Are Hh Preschool Children At Risk For Psychosocial Difficultmentioning
confidence: 99%
“…However, it is important to recognise that, although at increased risk at a group level, the majority of those with PCHL do not show clinically significant EBD (van Gent, Goedhart, Hindley, & Treffers, 2007; Stevenson et al., in press). In cross‐sectional analyses, we have shown that in middle childhood (Stevenson, McCann, Watkin, Worsfold, & Kennedy, 2010) and in adolescence (Stevenson et al., 2017) that within the PCHL group those with less well developed receptive language are more likely to have EBD.…”
Section: Introductionmentioning
confidence: 98%
“…Those with PCHL also showed significantly higher scores on the SDQ than the HCG at both age groups 6–10 years (Stevenson et al., 2011) and 13–19 years (Stevenson et al., 2017). In addition, at both these age groups there was a strong association between the behaviour and receptive language abilities of the PCHL participants (Stevenson et al., 2010; Stevenson et al., 2017). Indeed, the elevated rate of behaviour problems shown by those with PCHL compared to the HCG was reduced to nonsignificance once differences in receptive language ability were taken into account.…”
Section: Introductionmentioning
confidence: 99%